Adherence to antiretroviral therapy and changes in body composition in people living with HIV and AIDS - Ferreira, Fernanda Carneiro Gomes; Souza, Sofia Oliveira de; Vasconcelos, Érica Priscila Carneiro Ouriques de; Santos, Ana Célia Oliveira dos (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The successful treatment of human immunodeficiency virus (HIV) infection depends on adherence to antiretroviral therapy. Since the development of ART, there has been a significant increase in the survival of people living with HIV/AIDS. However, in the same way that it works in a positive way, the antiretroviral therapy has side effects that ultimately influence the rate of adherence to drug treatment. Objective: Evaluate adherence to antiretroviral therapy (ART) and changes in the body composition of adults diagnosed with HIV/AIDSon ART for at least 12 months. Methods: A cross-sectional study was conducted at an outpatient clinic for infectious-parasitic diseases at a teaching hospital that is a reference in the treatment of people living with HIV/ AIDS. Socio-demographic and clinical data were collected from medical records. Weight, height, body mass index (BMI) and abdominal circumference (AC) were recorded. Bioelectrical impedance analysis was performed using the tetrapolar protocol to assess body composition. The “Cuestionario para la Evaluación de la Adhesión al Tratamiento Antiretroviral” was used to investigate adherence to ART. Results: Sixty-one patients (27 women and 33 men) participated in the study. Most were more than 40 years of age and were classified as overweight based on BMI. Most patients (86.8%) had been using ART for more than five years and 78.6% were classified as sedentary. Among the patients with an adequate AC, 82.3% were men. Among the 11 patients with low adherence to ART, 90.9% were men. Among the 33 with strict adherence, 69.6% were women. Mean percentage of fat mass was 28.63% among the men, and 40.82% among the women. Conclusion: Strict adherence to ART was seen in more than half of the study population. Women had more side effects from ART, as this group hadgreater adherence to treatment. The findings underscore the relationship between high rates of adherence to ART and changes in body composition, such as increased fat deposition and risk of associated diseases.